Penilaian Risiko Aplikasi Web Menggunakan Model DREAD - Suprihanto, Didit; Prahasto, Toni; Sugiharto, Aris (JSINBIS (Jurnal Sistem Informasi Bisnis), 2013)
Application thatÂ  is developed by web based, beside has surplus in WWW technology, it has susceptibility side that can be threat too. Susceptibility generate risk and can bring out big trouble even effect big disadvantage. The goal of this research is design and build document risk assessment system of threat level and prevention advice. It use DREAD model as method to solve trouble by giving qualified information. This information are used to produce risk level in web application. The result of this research is web application risk assessment system by using DREAD model to know risk threat level and equate perception of web threat risk to application developer, minimize of threat risk and maximize performance of web application. Â  Keywords : DREAD model, web threat risk, web risk assessment system